Une plage à Genève. Oui, mais quelle plage ? - Simon Gaberell; Joëlle Salomon Cavin (Projets de Paysage)
In 2009, the Geneva authorities launched a project to install a beach in the centre of the city on the banks of Lake Leman. Although a consensus was soon reached regarding the benefits of such a project in Geneva, public controversy emerged concerning the ecological impact of the project. This controversy is linked to the different points of view of nature experts. A difference in the appreciation of the value of the biodiversity of the lake compared with the social benefits of the beach project is at the origin of this controversy. Defined based on a qualitative survey conducted among naturalists involved in the controversy, three types of notions shed light on the values associated with nature in urban areas : (1) a defensive concept of nature in the city, associated with the idea of a suspended pontoon ; (2) an integrated notion embodied by the installation of a shore, constituting a transition between the beach and the lake ; (3) a utilitarian concept associated with the creation of a park with a lawn. Whereas many studies have demonstrated the benefits of approaching development projects via the notion of the landscape, which makes it possible to combine social and biological concerns, this controversy shows that combining such aspects remains a focus of debate among naturalists.